Aplikasi Sistem Pakar Analisis Kulit Muka - Amir Khan, Amal Hazirah; Norlida Hassan, (Applied Information Technology And Computer Science, 2021)
There is dumping of sales of facial skin products that contain harmful substances on the market out there. Apart from that, some products do not get approval from the Ministry of Health Malaysia (MOH). These dangerous products have also received a lot of mass media coverage for example on radio and television stations. However, the National Pharmaceutical Regulatory Division of the MOH actively conducts inspections and cancels the notification of the product. In addition, the MOH has also provided awareness to the public by urging them to avoid any purchase of some cosmetic products that have been blacklisted. This shows that the MOH is very sensitive and serious about issues like this but it turns to consumers not to take shortcuts to have a bright face and can cause harm and risk to kidney function. Based on the issue, this expert system application was developed not only for users to know the cause of the skin problems they face but it is also able to provide treatment recommendations and ingredients needed in facial products. In addition, this application can provide correct information on how to care for facial skin. The application has covered all the information that users want to search. Users only need to enter the symptoms that will be used to diagnose the correct way of treatment as well as the appropriate material for the problem they are facing. The application uses knowledge-based and knowledge-based engineering methodologies as well as uses forward chain techniques. This application uses the android studio as the main software and java as the programming language and firebase to store the data. In conclusion, this app can give an awareness that understanding each other’s skin is more important than relying on others to understand our skin.